Diurnal and semi-diurnal coordinate variations observed in EUREF permanent GPS network – a case study for period from 2004.0 to 2006.9 - HEFTY, Ján; IGONDOVÁ, Miroslava (Contributions to Geophysics and Geodesy, 2010)
The 2.9-year interval of homogeneous and continuous observations at 29 European permanent GPS stations distributed all over the whole continent is analyzed for the short-periodic variations of site coordinates. In the literature seasonal terms in GPS coordinate series are well documented; the main objective of this paper is to investigate the existence of variations with shorter periods. We used the coordinate estimates obtained from 4-hour observing intervals which enabled identification of variations with diurnal and sub-diurnal periods. In the amplitude spectra of station time series we detected a set of dominant periodic terms which have exclusively diurnal and semi-diurnal tidal frequencies. The most significant are the diurnal S1, K1, O1 and semi-diurnal S2, K2, M2 waves. Their amplitudes are different for individual sites and they reach from sub-millimetre values up to ∼ 3 mm for some stations situated close to the Atlantic coast. Uncertainties of estimated amplitudes are generally at the 0.3 mm level. The possible origin of the observed periodic variations is very complex. We interpret the observed coordinate variability as a superposition of potential deficiencies in used models of ocean tide loading displacements, effects of atmospheric tides, multipath, troposphere and ionosphere residual effects, and other phenomena with diurnal and semi-diurnal forcing as well as the unidentified GPS analysis imperfection. The geokinematical relevance of detected variations and their possible interpretation are discussed.